Pengaruh Kualitas Pelayanan Terhadap Kepuasan Mahasiswa Universitas Pamulang - Ike Riskyanti; Muhamad Faisal Fahmi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to examine the effect of service quality on student satisfaction at Pamulang University. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to 100 students from various study programs. The independent variable in this study is service quality (x) quality with sub variables including: reliability, tangible, responsiveness, assurance and empathy. While for the dependent variable (Y) is student satisfaction. The results of data analysis show that service quality has a positive and significant effect on student satisfaction. The results of the statistical analysis obtained a determination coefficient value of 55.6% which illustrates that the factors in the independent variables have a large influence on service satisfaction. Furthermore, based on the hypothesis test, the results show that there is a significant effect of service quality on satisfaction.